Heavy Metals, Trace Elements and Biochemical Composition of Different Honey Produce in Turkey - Sahinler, Nuray; Gul, Aziz; Akyol, Ethem; Oksnz, Abdullah (Asian Journal of Chemistry, 2010)
In this work, the biochemical composition, trace elements and heavy metal contents of honey samples, which were collected from different regions and different botanical origin in Turkey were evaluated. The average content of minerals, moisture, acidity, hydroxymethylfurfural, diastase, invert sugar, pH, sucrose, electrical conductivity and heavy metal contents were determined. The biochemical composition of different botanical originated honeys were determined within the limits of Turkish Standard Institution (TSE), CODEX and EU standards. Level of invert sugar in cotton honey and sucrose level in sunflower honey weren't found agree with TSE and EU standards. In addition to biochemical compositions, the presence of Al, Ba, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn were determined agree with ICP AES. The highest value of Cr, Cu, K, Mn, Na and Al, contents were found in pine honeydew honey with a levels of 0.50, 2.14, 1931, 1.46, 285, 7.49 mg kg-1, respectively. The highest level of Cd, Co, Mg, Ni and Pb (0.32, 0.22, 103, 0.64, 1.29 mg kg-1) were found in cotton honey. The highest level of Ba and Zn were determined in multifloral honey with a level of 1.47 ppm and 3.29 ppm, respectively. K, Na and Mg were the major macro elements in all honey samples. This study showed that the source of nectar and ecological regions have an important effect on the biochemical compositions, trace elements and heavy metals contents of honey.